2006
DOI: 10.1002/pat.841
|View full text |Cite
|
Sign up to set email alerts
|

Organic/inorganic nanocomposites prepared by mechanical smashing of agglomerated silica ultrafine particles in molten thermoplastic resin

Abstract: A new approach for the preparation of organic/inorganic nanocomposites was investigated in which nano-sized silica particles without surface modification were dispersed by the mechanical smashing of strength-controlled porous silica agglomerates in molten resin during direct melt-compounding. The method consists of two stages. The first stage involves preparation of the strength-controlled agglomerated silica nanoparticles with pore structure, and the second stage involves meltcompounding of a thermoplastic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
31
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 51 publications
0
31
0
1
Order By: Relevance
“…16,17 In fact, it has been shown that a considerable improvement in polymer nanocomposite mechanical properties can be achieved by adding nanosized fillers, such as SiO 2 and ZnO, at low volume content, i.e. in the range 1-5 vol%, [18][19][20] which is very important due to the high cost of nanosized fillers.…”
mentioning
confidence: 99%
“…16,17 In fact, it has been shown that a considerable improvement in polymer nanocomposite mechanical properties can be achieved by adding nanosized fillers, such as SiO 2 and ZnO, at low volume content, i.e. in the range 1-5 vol%, [18][19][20] which is very important due to the high cost of nanosized fillers.…”
mentioning
confidence: 99%
“…Therefore, the author’s research group has focused on the fracture strength of agglomerates of the dispersed nanoparticles (required stress for the breakdown of the agglomerates into nano-sized primary particles) [60,61,62,63,64,65,66]. For this method, the preparation stage of the strength-controlled agglomerates with a porous structure (the first stage) was combined with the melt-compounding process (the second stage).…”
Section: Simple Melt-compounding Without Surface Modification Of Nmentioning
confidence: 99%
“…On the basis of the chemistry of colloidal silica [84] and the DLVO (Derjaguin-Landau-Verwey-Overbeek) theory on the stability of a colloidal dispersion system [86,87], the packing structure of the agglomerate was controlled, ensuring open packing with a large amount of porosity. In the following section, the experimental techniques and the main findings of the previous studies carried out by the author and coworkers [60,61,62,63,64] are reviewed together with the results on the dispersion state of silica particles into various polymers by melt-compounding each polymer with the prepared agglomerates.…”
Section: Simple Melt-compounding Without Surface Modification Of Nmentioning
confidence: 99%
“…Tanahashi et al 16 pointed out that the application of nanosized fillers demonstrated the potential to improve the general performance of thermoplastic polymers fundamentally. It has been shown that a considerable improvement of mechanical properties can be achieved by adding a low volume content of nanosized fillers, somewhere in the range of 1 -5 vol %.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of the conducting PVK with dark green color, in which the polymer chain is formed exclusively by bonds between benzene rings, is possible. [12][13][14][15][16] It has been reported that blending polymer with inorganic materials is considered as a powerful method to produce new materials called polymercomposites or filled polymers. However, due to the significant development in nanotechnologies in the recent years, nanoinorganic materials such as SiO2, Al2O3 and TiO 2 have brought much attention to this research field.…”
Section: Introductionmentioning
confidence: 99%